The Role of Village-Owned Enterprises for the Welfare of the Community of Aek Banir Village, Panyabungan District - Siti Kholijah (Jurnal Mantik, 2022)
The income of "Serba Indah" Village-Owned Enterprises still does not have much effect on the income of "Serba Indah" Village-Owned Enterprises because the proceeds from the sale of ant sugar are still used to add to the completeness of existing goods. Utilizing Village-Owned Enterprises "Serba Indah" is one of the efforts to improve the community's economy. Village-Owned Enterprises should impact change and welfare in the community's economy. This study aims to determine the role of Village-Owned Enterprises toward the welfare of the community in Aek Banir Village, Panyabungan District, and the role of Village Owned Enterprises in the welfare of the community from the perspective of sharia economic law. This research was conducted using a descriptive qualitative approach, where this research was conducted in Aek Banir Village, Panyabungan District. The Village Owned Enterprise “Serba Indah” helps the welfare of palm sugar craftsmen who are in the field of making palm sugar. Through the Village-Owned Enterprises "Serba Indah," it is easier for them to market their products. Some people do not know the role of Village Owned Enterprises. The lack of public knowledge proves that the community's welfare is not evenly distributed.